2008
DOI: 10.1177/1753193408096021
|View full text |Cite
|
Sign up to set email alerts
|

Reanimation of Thumb Extension after Upper Extremity Degloving Injury Treated with Integra®

Abstract: A case of severe degloving injury to the left hand with complete destruction of the extensor apparatus of the thumb and exposure of the IP joint is presented. The damaged area was resurfaced with the use of the Integra template and the abductor pollicis longus tendon, lengthened with a tendon graft provided by the extensor indicis, and used to restore thumb extension. The transfer was performed through a prefabricated sheath under the Integra resurfaced area in a two-staged procedure. The final result was func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Integra® was applied directly on flexor tendons without paratenon and the median nerve, with a reported excellent outcome. Katrana et al (2008) reported a satisfying aesthetic and functional final result in a severe case of a severe third-degree burn to the left hand in a 45-year-old man resulting in a degloving injury with complete destruction of the extensor apparatus of the thumb and exposure of the proximal interphalangeal joint. They successfully restore extension and flexion (ROM: MP 0–45° and IP 0–30°) combining the use of Integra® with a tendon graft provided by the extensor indicis.…”
Section: Discussionmentioning
confidence: 99%
“…Integra® was applied directly on flexor tendons without paratenon and the median nerve, with a reported excellent outcome. Katrana et al (2008) reported a satisfying aesthetic and functional final result in a severe case of a severe third-degree burn to the left hand in a 45-year-old man resulting in a degloving injury with complete destruction of the extensor apparatus of the thumb and exposure of the proximal interphalangeal joint. They successfully restore extension and flexion (ROM: MP 0–45° and IP 0–30°) combining the use of Integra® with a tendon graft provided by the extensor indicis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of these devices, especially the first, appears to be steadily increasing in clinics around the world (e.g. Katrana et al 2008;Sasidaran et al 2008;Wakabayashi et al 2008;Baldwin et al 2009). …”
Section: (C) Established Clinical Usesmentioning
confidence: 99%
“…It is designed to act as a skin regeneration scaffold that allows the host's cells to grow into the dermal template. Although it was initially approved by the Food and Drug Administration to treat burn injuries [4], its indications continue to expand due to numerous accounts of desirable clinical and histologic outcomes [25, 7, 1113, 17, 19, 20]. Currently, its use spans multiple areas of reconstructive surgery, including soft tissue coverage following tumor excision [25, 7, 1113, 17], soft tissue coverage following the repair of congenital defects [11], and traumatic loss of soft tissue [3, 12, 19, 20].…”
Section: Introductionmentioning
confidence: 99%